2020
DOI: 10.1002/bin.1712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research on behavioral activation as treatment for post‐traumatic stress disorder: A brief review and meta‐analysis

Abstract: Behavioral activation (BA), an effective treatment for depression, has recently been receiving attention as a possible intervention for PTSD. BA interventions could be particularly useful in treating underserved populations (i.e., individuals with lower socioeconomic status). A literature search was conducted, which identified seven outcome studies that examined the effectiveness of stand-alone BA treatment for individuals with PTSD. All studies identified for this brief review demonstrated clinically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Indeed, one possible explanation for this is the social causation theory, i.e. that having more social support or more pleasant interactions alleviated PTS (Flint et al, 2020 ). Alternatively, it is possible that survivors with lower PTS may have been less likely to avoid social interaction or that survivors with higher PTS may have found that others were less willing to engage in social interactions with them (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one possible explanation for this is the social causation theory, i.e. that having more social support or more pleasant interactions alleviated PTS (Flint et al, 2020 ). Alternatively, it is possible that survivors with lower PTS may have been less likely to avoid social interaction or that survivors with higher PTS may have found that others were less willing to engage in social interactions with them (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, behavioral activation teaches participants how to identify and engage in activities that are supportive and consistent with their values and goals to reduce prevention and isolation (Cuijpers et al, 2020). A meta-analysis of behavioral activation for PTSD symptoms found that symptoms were significantly decreased, with an average reduction of 25.8 % (Flint et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Total score ranges from 0 to 27, where high scores mean higher possibility of depression. The total score can then be interpreted as suggesting no depression (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), or severe (20)(21)(22)(23)(24)(25)(26)(27). A cut-off score of 10 is considered to indicate the possibility of depressive disorder.…”
Section: Patient Health Questionnaire-9 (Phq-9)mentioning
confidence: 99%
“…While behavioral activation was originally developed for depression and has well-established empirical support ( Simmonds-Buckley et al, 2019 , Stein et al, 2020 ), including successful delivery via the Internet ( Huguet et al, 2018 ), more recently, behavioral activation has been studied as an intervention for PTSD. A meta-analysis of behavioral activation for PTSD symptoms found significant reductions in PTSD symptoms with an average symptom reduction of 25.8% ( Flint et al, 2020 ). Another small meta-analysis of three studies found large effect size improvements in PTSD symptoms compared to wait-list controls ( Etherton & Farley, 2020 ).…”
Section: Evidence-based Psychological and Behavioral Strategiesmentioning
confidence: 99%